Essays on international trade and the economics of conflict - Luo, Zijun (Kansas State University, 2012)
This dissertation comprises three chapters in international trade and the economics of conflict. These chapters are put together according to two dimensions. From the international relations dimension, Chapter 1 analyzes free trade, which is the most “liberal” form of international relation; Chapter 2 analyzes different types of trade agreements, which is the most common and “moderate” form of international relation; and Chapter 3 analyzes conflict, which is the most violent and “extreme” form of international relation. From the proximity dimension, free trade usually occurs between countries that are far from each other, trade agreements usually signed by countries with in a region, and conflict usually happens between two very close countries. Chapter 1 develops a novel model of international trade in which transportation costs are driven by trade imbalance of an individual country. This task is accomplished by assuming a representative transportation firm in each country that competes with its counterparts from other countries for international operation. The model of trade imbalance driven costs complements results from traditional international trade model in that it sheds light on how trade costs are affected by country size. With multiple countries and a continuum of production firms in each country under monopolistic competition, we derive an index of transportation costs to capture bilateral trade barriers for country pairs. This index is time-variant, which makes it suitable for panel data studies. Based on the index, simulation and simplified three-country free trade model show that countries with a relatively larger size incur a trade deficit while smaller size implies a trade surplus under free trade. A gravity equation is derived and estimated using Poisson Pseudo Maximum Likelihood. Estimation results support the fitness and robustness of the theoretical model of trade using the constructed transportation cost index. Further, statistical test shows that this transportation cost index is a better approximation of bilateral trade cost than distance. A growing number of recent regional trade agreements (RTAs) have introduced provisions concerning cross-border investments. Likewise, a substantial number of RTAs have been preceded by agreements regarding cross-border investments. In Chapter 2, we develop a partial equilibrium three-country model to examine the relationship between RTAs and FDI while also allowing for double taxation. Our analysis shows that the formation of an RTA between two regional countries with wage asymmetry is welfare-improving for the low-wage country and the region, but can be welfare-deteriorating for the high-wage country. We extend our analysis to examine the role of repatriation taxes in the determination of firm location when an RTA is and is not established. Our final result suggests that the signing of an RTA would not induce the relocation of a plant from the high-wage country to the low-wage country unless a reduction of the repatriation tax rate also occurs. In Chapter 3, we attempt to resolve the “inefficiency puzzle of war” by developing a general equilibrium model of bargaining and fighting with endogenous destruction. In the analysis, we consider the scenario that two contending parties engage in bargaining to avoid fighting when there are direct costs (e.g., arms buildups) and indirect costs (e.g., destruction to consumable resources) of conflict. Taking into account different modes of “destruction technology” (in terms of weapons’ destructiveness) without imposing specific functional form restrictions on conflict technology and production technology, we characterize their interactions in determining the Nash equilibrium choice between fighting and bargaining. We find that bargaining is costly as the contending parties always allocate more resources to arming for guarding their settlement through bargaining (but under the shadow of conflict) than in the event of fighting. Contrary to conventional thinking that bargaining is Pareto superior over fighting, we show conditions under which fighting dominates bargaining as the Nash equilibrium choice. The positive analysis may help explain the general causes of fighting, strikes, international conflict, and wars without incomplete information or misperceptions.
Keywords: International trade; Conflict; Transportation cost; Foreign direct investment; Economics (0501)